EFL Teachers Teach Heterogeneous Classroom in One Junior High School in Medan: A Phenomenological Study - Risa Anggraini (Journal MELT (Medium for English Language Teaching), 2022)
Teachers, of course, need to have some ways in handling students with various skills in a classroom. This research was done in One Junior High School in Medan. There were five EFL teachers participated in this study. Researcher used a qualitative which focused on phenomenology as the research method. Some findings were categorized into some themes. The findings showed some students’ diversity aspects such as Current Level of English, Potential Learning Ability, Motivation, Learner Independence and Autonomy Personality, Learning Style, Confidence, Discipline and Interest. These aspects of diversity were according to Goncharova’s theory (2003). These findings also indicated that teachers ought to motivate their students to result on the performance of the students in teaching and learning process and  Furthermore, teachers should have strategies that can take students’ interests to study. Most importantly, teachers needed to be able to understand each of their students well because teachers have to cooperate with all mixed-ability students well during the teaching and learning process. In short, teachers can take advantage of approaching and talking in personal, creating more enjoyable activities and making a contract of language-learning with the students whose very uncooperative. EFL teachers who face the heterogenous classes do not need to be perturbed on how to manage students with different ability. The more teachers apply a mixture of strategies, the easier they teach the heterogenous classes and the better the learning outcome will be.